2003
DOI: 10.1002/adma.200305346
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectricity in Highly Stressed Quasi‐Amorphous Thin Films

Abstract: Spontaneous or stress-induced polarization, signifying pyroelectricity and piezoelectricity, respectively, can appear in ionic solids solely due to a non-centrosymmetrical spatial distribution of ions in a polar crystalline structure. Although theory does not impose strict limitations on the size of a polar crystallite, [1,2] the magnitude of pyroelectric and piezoelectric effects of some ceramics, particularly BaTiO 3 , rapidly decrease as grain size diminishes to a few nanometers. [1,3,4] Determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…Recently, Lubomirsky and coworkers [75,[94][95][96] presented experimental data on perovskite thin films, which strongly suggest that a strain gradient can pole an amorphous material when it is thermally treated in a special way. It was shown that during such treatment the material is passing between two different amorphous states.…”
Section: Plastic Flexoelectricitymentioning
confidence: 99%
“…Recently, Lubomirsky and coworkers [75,[94][95][96] presented experimental data on perovskite thin films, which strongly suggest that a strain gradient can pole an amorphous material when it is thermally treated in a special way. It was shown that during such treatment the material is passing between two different amorphous states.…”
Section: Plastic Flexoelectricitymentioning
confidence: 99%
“…However, the commonly accepted wisdom that inorganic solids may only be pyro-and piezoelectric in crystalline form has recently required reconsideration following the report that noncrystalline pyro-and piezoelectric thin films of BaTiO 3 could be prepared on Si substrates. [3] Subsequent investigation of this phase, called quasiamorphous, [4][5][6][7] revealed that amorphous thin films of BaTiO 3 prepared by sputtering contain a network of randomly connected TiO 6 octahedral local bonding units. These TiO 6 octahedra are slightly distorted and, therefore, polar.…”
mentioning
confidence: 99%
“…SrTiO 3 differs from BaTiO 3 with respect to the stabilizing cation (Sr instead of Ba). The experimental procedure for preparation of the quasiamorphous phases of BaZrO 3 and SrTiO 3 was similar to that developed for the synthesis of the quasiamorphous phase of BaTiO 3 . [3][4][5]7] Amorphous films of SrTiO 3 or BaZrO 3 (50-200 nm thick) were deposited by radiofrequency magnetron sputtering on highly conductive (>0.01 X cm -1 ) Si substrates.…”
mentioning
confidence: 99%
See 2 more Smart Citations